Syndecan-1 alters heparan sulfate composition and signaling pathways in malignant mesothelioma - Heidari-Hamedani, G.; Vives, R. R.; Seffouh, A.; Afratis, N. A.; Oosterhof, A.; van Kuppevelt, T. H.; Karamanos, N. K.; Metintas, M.; Hjerpe, A.; Dobra, K.; Szatmari, T. (Cell SignalCell Signal, 2015)
Syndecan-1 is a proteoglycan that acts as co-receptor through its heparan sulfate (HS) chains and plays important roles in cancer. HS chains are highly variable in length and sulfation pattern. This variability is enhanced by the SULF1/2 enzymes, which remove 6-O-sulfates from HS. We used malignant mesothelioma, an aggressive tumor with poor prognosis, as a model and demonstrated that syndecan-1 over-expression down-regulates SULF1 and alters the HS biosynthetic machinery. Biochemical characterization revealed a 2.7-fold reduction in HS content upon syndecan-1 over-expression, but an overall increase in sulfation. Consistent with low SULF1 levels, trisulfated disaccharides increased 2.5-fold. ERK1/2 activity was enhanced 6-fold. Counteracting ERK activation, Akt, WNK1, and c-Jun were inhibited. The net effect of these changes manifested in G1 cell cycle arrest. Studies of pleural effusions showed that SULF1 levels are lower in pleural malignancies compared to benign conditions and inversely correlate with the amounts of syndecan-1, suggesting important roles for syndecan-1 and SULF1 in malignant mesothelioma.
Keywords: *Signal Transduction; Biosynthetic Pathways; Cell Cycle; Cell Line, Tumor; gene expression; Gene Expression Regulation, Neoplastic; Heparitin Sulfate/*metabolism; Humans; Kaplan-Meier Estimate; Lung Neoplasms/*metabolism/mortality; Malignant mesothelioma; Mesothelioma, Malignant; Mesothelioma/*metabolism/mortality; Mitogen-activated protein kinase (MAPK); Pleural Effusion, Malignant/metabolism; Proportional Hazards Models; Receptor tyrosine kinase; Sulfotransferases/metabolism; Syndecan-1; Syndecan-1/*physiology; Transcription factor